(untitled) (Fiep Bulletin - online, 2017)
The aim of the article is to analyze the existence of projects and programs related to the personal and socialdevelopment of Physical Education teachers that are organized by The Ministry of Education, Science, Research and Sport ofthe Slovak Republic. We found out that from 22 projects undertaken in the program period 2007 - 2013, whose activities couldcontinue to be implemented until the end of 2015, none was primarily related to this area of education. Only 53 programs under 2selected projects were related to the personal and social development. Personality development of PE teachers is one of the keyfactors in making the educational process successful.